Systemic immune-inflammatory biomarkers assist in differentiating clinical features of different etiologies of acute kidney injury: results from eICU Collaborative Research Database - Qiqiang Liang; Sumian Zhang; Xuebin Wang (Renal Failure)
Background The relationship between distinct etiologies of acute kidney injury (AKI) and systemic immune-inflammatory biomarkers remains poorly defined.Methods We performed a retrospective cohort study utilizing the eICU Collaborative Research Database (eICU-CRD), a multicenter U.S. dataset. The study included all patients diagnosed with AKI while excluding those with unclear AKI etiology or chronic kidney disease. Analyzed variables encompassed demographic characteristics, admission/discharge data, laboratory parameters, severity scores, and comorbidities. We specifically evaluated four clinically accessible systemic immune-inflammatory indices. Intergroup differences were assessed using letter notations, nonlinear relationships were explored via restricted cubic spline models, and confounding variables were controlled for using propensity score matching.Results The analysis included 2,912 patients with AKI of known etiology, categorized into six etiological subgroups. Pairwise comparisons revealed significant differences (p < 0.001) in systemic immune-inflammatory biomarkers between a high-inflammation group (sepsis-associated AKI, acute tubular necrosis [ATN], hepatorenal syndrome) and other subgroups (hypovolemic, obstructive, ischemic, and drug-induced AKI). Notable disparities emerged for the systemic immune-inflammation index (SII) (4,120 vs. 3,340) and neutrophil-to-lymphocyte ratio (NLR) (19.1 vs. 14.7). Cox regression identified independent predictors of mortality: membership in the high-inflammation group (Odds Ratio [OR] = 1.67, 95% Confidence Interval [CI] = 1.39–2.00) and septic shock (OR = 1.65, 95% CI = 1.46–1.84). Following propensity score matching, the high-inflammation group remained a significant independent risk factor for mortality.Conclusion Patients with AKI primarily attributed to sepsis, ATN, or hepatorenal syndrome constitute a high-inflammation subgroup characterized by elevated systemic immune-inflammatory biomarkers. This subgroup independently predicts increased mortality risk.